O percurso histórico da criação do curso de ciências biológicas no Brasil e os desafios e possibilidades na formação profissional no IFAP - Campus Laranjal do Jari - SANTOS JUNIOR, Lucas Silva (2023)
Among all the existing degree courses, the degree course in Biological Sciences presents a range of activities in the job market in addition to teaching, which allows them to work as biologists. The present work aimed to evaluate the main doubts of biological science degree students at IFAP – Campus Jari about the profession and field of activity of the biologist, and based on these doubts, an educational material was prepared in the form of a booklet that can guide and resolve doubts. of students who identify with this profession. The research carried out was qualitative and exploratory-descriptive, where information was collected in two moments: during a lecture and during the application of an online questionnaire. The data obtained in the lecture were used to create an educational product in the form of a booklet and the questionnaire evaluated the opinion about the product generated. A total of eight individuals participated in the research, whose main doubts about the profession of biologist were related to the requirements to be a biologist, where the biologist works and how to enter the job market. A total of three categories of opinions were formed during the analysis of the booklet evaluation responses: doubts resolved, irrelevance of content and novelty of the content. The educational product created presented, in a general context, good acceptance by the target audience and fulfilled the objectives proposed in the work.